Concomitant Transmission of Dengue, Chikungunya, and Zika Viruses in Brazil: Clinical and Epidemiological Findings From Surveillance for Acute Febrile Illness. (18th December 2018) - Silva, Monaíse M O; Tauro, Laura B; Kikuti, Mariana; Anjos, Rosângela O; Santos, Viviane C; Gonçalves, Thaiza S F; Paploski, Igor A D; Moreira, Patrícia S S; Nascimento, Leile C J; Campos, Gúbio S; Ko, Albert I; Weaver, Scott C; et al.
Abstract: Background: Since their emergence in the Americas, chikungunya (CHIKV) and Zika (ZIKV) viruses co-circulate with dengue virus (DENV), hampering clinical diagnosis. We investigated clinical and epidemiological characteristics of arboviral infections during the introduction and spread of CHIKV and ZIKV through northeastern Brazil. Methods: Surveillance for arboviral diseases among febrile patients was performed at an emergency health unit of Salvador, Brazil, between September 2014 and July 2016. We interviewed patients to collect data on symptoms, reviewed medical records to obtain the presumptive diagnoses, and performed molecular and serological testing to confirm DENV, CHIKV, ZIKV, or nonspecific flavivirus (FLAV) diagnosis. Results: Of 948 participants, 247 (26.1%) had an acute infection, of which 224 (23.6%) were single infections (DENV, 32 [3.4%]; CHIKV, 159 [16.7%]; ZIKV, 13 [1.4%]; and FLAV, 20 [2.1%]) and 23 (2.4%) coinfections (DENV/CHIKV, 13 [1.4%]; CHIKV/FLAV, 9 [0.9%]; and DENV/ZIKV, 1 [0.1%]). An additional 133 (14.0%) patients had serological evidence for a recent arboviral infection. Patients with ZIKV presented with rash and pruritus (69.2% each) more frequently than those with DENV (37.5% and 31.2%, respectively) and CHIKV (22.9% and 14.7%, respectively) ( P < .001 for both comparisons). Conversely, arthralgia was more common in CHIKV (94.9%) and FLAV/CHIKV (100.0%) than in DENV (59.4%) and ZIKV (53.8%) ( P < .001). A correct presumptive clinical diagnosis was made for 9%–23% of the confirmed patients. Conclusions: Arboviral infections are frequent causes of febrile illness. Coinfections are not rare events during periods of intense, concomitant arboviral transmission. Given the challenge to clinically distinguish these infections, there is an urgent need for rapid, point-of-care, multiplex diagnostics. Abstract : Simultaneous transmission of dengue, chikungunya, and Zika viruses occurs in endemic regions, leading to frequent coinfections. Rash and pruritus are more common with Zika, while arthralgia is more common with chikungunya. Nevertheless, correct medical diagnosis is challenging without laboratory testing.